Sistema FiME associado a aplicação do coagulante Moringa oleifera e do sulfato de alumínio no tratamento de água de abastecimento - Vizibelli, Dandley (2021)
As a result of the exponential growth of the human population in recent years, there has been a greater increase in the deterioration of water sources and bodies of water used for supply, a factor that especially harms populations residents in places further away from large urban centers, and have greater difficulty in accessing treated water. In this view, this study aims to find greater employability for the Multi-Step Filtration (FiME) technique, allowing water with higher concentrations of particles to be treated through the use of the coagulation step in the system, comparing the non-use of coagulants (C1) and the use of coagulants such as Aluminum sulphate (C2) and Moringa oleifera seed (C3) at concentrations of 6mg.L-1 and 80mg.L-1 , respectively, in filtration rows carried out in a FiME system supplied with synthetic water. This system was constituted by the stages of dynamic pre-filter (PFD), gravel pre-filter (PFA) and slow filters, these differentiated from each other by the composition of the support layer composed of geotextile non-woven (FL1) or granular material (FL2). The parameters observed during the experiments were temperature, pH, electrical conductivity, apparent color, turbidity, total solids, total suspended and total dissolved, in addition to head loss in the slow filters. Among these, the temperature and pH did not show great variations, where the second remained within the limits established by legislation; electrical conductivity showed changes only in C3. The apparent color, turbidity and solids data demonstrated that the application of coagulants was efficient in order to reduce the solids load at the entrance of the slow filters. The difference support layer configurations between the slow filters did not provide a significant difference between the efficiency values registered in the parameters relative color, turbidity and solids. The apparent color removal efficiency data provided by the treatments showed no significant difference between them, with final values remaining between 6.0 and 9.0uH. The turbidity removal efficiency data demonstrate that the C3 treatment statistically presented the best results, registering final values of 1.65± 0.46 and 1.39± 0.47uT, followed by the C2 data with 3.07± 0.87 and 2.87± 0.73uT and C1 with 5.17± 0.77 and 5.08± 0.45uT, FL1 and FL2 respectively. When the pressure loss parameter was observed, the shortest treatment duration occurred in C3, where the maximum load loss was reached in 15(FL1) and 17(FL2) days, C1 reached the maximum load loss in 18(FL1) and 19 (FL2) days. During the 21 days of proposed treatments, C2 did not reach the maximum pressure loss value of 15cm, recording final values of 3.4(FL1) and 3.8(FL2) cm. The results proved that the addition of coagulants contributed to the amortization of turbidity peaks and an increase in the turbidity range where filters can be used. For the use of the coagulant extracted from the seed of Moringa oleifera, where better results of turbidity removal efficiency were observed, it is still necessary to advance in the reduction of the solids load added to the system through its coagulant solution, in order to allow greater length of the filtration run.